Representation of the Holocaust in Soviet literature and film : [based on lectures presented at the International Conference "The Holocaust and the Jews in the Second World War in Soviet Literature and Film" that took place at Yad Vashem on february 19 - 20, 2013, Jerusalem] - Grinberg, Marat 1977-; Toker, Leona 1950-; Tippner, Anja 1963-; Ḳoṭlerman, Ber Boris 1971-; Gershenson, Olga 1969-; Yad Vashem; International Conference "The Holocaust and the Jews in the Second World War in Soviet Literature and Film" (Search and research, 2013)
Rabbis celebrated and condemned : Boris Slutsky's response to Il'ia Sel'vinskii / Marat Grinberg -- On the eve of the moratorium : the representation of the Holocaust in Ilya Ehrenburg's novel "The storm" / Leona Toker -- The writings of a Soviet Anne Frank? Masha Rol'nikaite's Holocaust memoir "I have to tell" and its place in Soviet literature / Anja Tippner -- "My people will be reborn here" : World War II and Jews in the Yiddish literature of Birobidzhan / Ber Kotlerman -- The Holocaust on Soviet screens : charting the map / Olga Gershenson